946 Social and Medical Risk Indicators in Adherence of HIV/AIDS Infected Children by Vertical Transmission. (October 2012) - Hirsch, R
Abstract : 50 children were assisted at Hospital Muniz from 8/1/2010 to 2/28/2011: 11 boys (2/12), 11 girls (5/12), 28 teenagers: 9 males (12/17), 19 females (12/18). A social and medical score to value the adherence vulnerability was applied with these categories: annual internments, increase of viral load, decrease of CD4, clinical pathologies, relation between severity of pathology and internment length, lack of taking and/or delivering a medication, poor care support, lack of assistance to Short-Scheduled Hospitalization Program (SSHP ). The results are: Low Score (< 3): 24 patients. Slight Score (3 to < 6): 7 patients. Moderate Score (6 to < 12) : 8 patients. High Score (>12 to < 24): 11 patients. Nobody with low score presents social risks . Social risks were presented in: 5 slight score patients. 6 moderate score patients. 11 patients with high score. Suffered poor care support: 16 patients: 6 under 12 (27.3%) and 10 adolescents, 7 women (36.8%) and 3 males (33.4%). Lack of taking and/or delivering a medication: 20 patients, 4 children under 12 years (18.2%), 16 adolescents, 8 women (42.1%) and 4 men (44.4%) and lack of control to the SSHP, 15 patients: 4 children under 12 (18.2%) and 15 adolescents, 8 women (42.1%) and 3 males (33.3%). Social and Medical risk in adherence indicators (shown at 2010 IAS Congress) adding the data provided by other disciplines managed to predict clinical evolution, to modify guidelines approach, to generate therapeutic strategies for monitoring at different ages, to follow ARV therapies in vertical transmission HIV/AIDS affected children.